Green Spaces and Urban Liveability in Sub-Saharan Africa: Lessons from Bafoussam I, Cameroon - Samba, Gideon; Fokeng, Reeves Meli; Nfor, Julius Tata; Ngwaimbi, Roland Chah (International Journal of Global Sustainability, 2022)
Urban green spaces support the development of cities in diverse ways. Considerable work has been done in recent years exploring the value of urban green space for health and wellbeing of urban centres across the world and in Sub-Saharan African countries in particular. This study is designed to examine the contribution of green spaces to city liveability in Bafoussam I Council. Data for the study were obtained through primary and secondary sources using a mixed design method of inquiry which combines both quantitative and qualitative approaches to explore data on urban green spaces in Bafoussam I. Purposive and simple random sampling techniques were used to select households for questionnaire administration. The data engendered were analyzed with descriptive and inferential statistics. The outcomes indicated that green spaces have significantly contributed to the health and wellbeing of the city dwellers in Bafoussam I Council. The main actors responsible for green spaces management in the municipality include government agencies, Bafoussam City Council, Municipal Council, the civil society, and Non-Governmental Organizations. In line with the 2022 African Nations Cup (AFCON) in Cameroon, this city-centre beautification has been stepped up. The Pearson moment Correlation used to test the hypothesis indicated a strong positive correlation at a calculated P-value .001, thus, green spaces have significant effects on the health and wellbeing of urban dwellers in Bafoussam I. The study concluded by emphasizing that stakeholders of green spaces in the municipality need to collaborate to take effective decisions that can be sustainable to ensure protection and equitable management of urban green environment to meet the need of the future generations in line with Sustainable Development Goal (SDG) 11.